Éléments de réflexions sur le rapport entre la poésie occitane contemporaine et le sacré. L’exemple de Joan Larzac - Pierre Molin (Revue des Langues Romanes)
Joan Larzac (1938-), in his poetry written during the 1960s and 1970s, expresses sometimes contradictory views. Between Marxist revolt and Christian mysticism, the poet’s work is nevertheless consistent in the effect it seeks: to express an absence, whether linguistic (Occitan) or sacred (God).